Differences in 200-m sprint running performance between outdoor and indoor venues - Ferro, A.; Floria, P. (The Journal of Strength and Conditioning Research, 2013)
Athletes' times in 200-m indoor races are greater than in outdoor races. The purpose of this study was to determine which 50-m sections were slower indoors than outdoors in 200-m sprint events and by how much. Using 2-dimensional photogrammetric techniques, a 50-m split-time analysis was made of the performance of 17 men and 16 women, all well-trained athletes, at 4 national competitions held over 5 years. The time taken to run the 0- to 50-m section was longer indoors than outdoors in women (6.89 ± 0.12 vs. 6.75 ± 0.04 seconds; p < 0.05) and in men (6.18 ± 0.10 vs. 6.08 ± 0.09 seconds; p < 0.05). Similarly, both women and men took more time to run the 100- to 150-m section indoors (6.03 ± 0.15 vs. 5.84 ± 0.06 seconds; p < 0.01, respectively) than outdoors (5.26 ± 0.15 vs. 5.06 ± 0.07 seconds; p < 0.01, respectively). Both sections indoors were run mostly on the curve. However, significant differences were not found in the split times for 50-100 and 150-200 m in either sex. In both categories, the relative average velocity (RAV), percentage of average velocity relative to the maximum velocity reached in the fastest section (50-100 m), was about 3% lower indoors than outdoors in 100- to 150-m section. The athletes' lower capacity to develop speed indoors could be caused specifically, by the curved 0- to 50-m and 100- to 150-m sections of the indoor track. Coaches could use these data as reference values there being few published data from high-level competitions. The RAV could be used by coaches to compare results among athletes of different levels and sexes.